Structural Error Corrections in an English Conversation Class - Ulfini, Niswi (Universitas Dian Nuswantoro, 2025)
This study explored the correction of structural errors in a beginner-level English conversation class at a private language school in Indonesia. Building on the premise that both positive and negative evidence (corrective feedback) are essential for second language acquisition, the research investigated whether all structural errors were corrected, the source of the corrections, the timing, and the strategies employed. The study observed six EFL students during an online class, focusing on their use of past tense expressions. Data were collected through classroom observations and video recordings and analyzed using deductive content analysis. The results indicate that not all structural errors were corrected; the teacher and students themselves were the primary agents of correction, with peer correction notably absent. Most corrections occurred during controlled practice activities, aligning with the class's accuracy-focused goals. Immediate correction was the predominant timing strategy, and explicit correction methods, such as metalinguistic comments and elicitation, were favored over more implicit approaches like recasting. The findings suggest the need for greater consistency in corrective feedback and highlight the potential benefits of incorporating peer correction and explicit corrective feedback in beginner-level speaking classes. However, the study's limitations include its focus on structural errors without considering student uptake of corrections or the reasons behind the teacher's selective correction approach. Further research could explore these aspects to provide a more comprehensive understanding of corrective feedback in language learning contexts.